Properties of the complex type II burst with rich herringbone structure within 3–33 MHz - Dorovskyy, V. V.; Melnik, V. M.; Konovalenko, O. O.; Brazhenko, A. I.; Panchenko, M.; Rucker, H. O.; Poedts, S.; Stanislavsky, A. A.; Mykhaylov, V. A. (Видавничий дім «Академперіодика», 2013)
Characteristics of the type II burst with “herringbone” structure observed on 7 June 2011 within 3−33 MHz are considered. The burst was recorded both by the two ground-based radiotelescopes (UTR-2, URAN-2) and the spaceborne STEREO radio receivers. For the first time, a detailed statistical analysis of main parameters of the herringbone sub-bursts of type II (duration and frequency drift rate) was performed at decameter wavelengths separately for those positively and negatively drifting ones. Another new result within these frequencies is the measured degree of circular polarization of fine structure type II bursts. A fine frequencystructure of the sub-bursts herringbone was found to besimilar to the so-called “fringes” in the solar S-bursts. From the characteristic wave-like oscillations of the type II back-bone the parameters of coronal streamers intersected by the shock wave were derived. Using the observational data from the STEREO and SOHO spacecraft, the speed and direction of the associated CME propagation were detected. From the ground-based radio observations the radial speed of type II burst source was found. As a result, possible location of the type II burst source was determined. In addition, the geoeffectiveness of the discussed solar event was estimated.